Protective Efficacy of Fresh and Aged Macerated Garlic Oils in Safflower Oil Against Intra-Abdominal Adhesions in Rats - Çalışkan, G. Ülke; Emin, Nuray (Pakistan Veterinary Journal, 2023)
This study aims to investigate the protective efficacy of fresh (FG) and aged (AG) Taşköprü Garlic (Allium sativum L.) macerated oils prepared in safflower oil at different concentrations against post-operative (PO) intra-abdominal adhesions (PIA). No commercial garlic product was used in the study. AG was produced from Taşköprü Garlic, which is one of the geographically indicated products of the European Union. Then FG and AG were kept at two different concentrations (1.5 g/mL & 2.0 g/mL) in safflower (Carthamus tinctorius L.) oil to get macerated oils of FG15, FG20, AG15 and AG20. After spectrophotometric and chromatographic analyzes of the oils, in vivo experiments were made on rats. A cecal abrasion model was applied to six study groups viz FG15, FG20, AG15, AG20, serum physiologic control and oil control. Their preventive activities against PIA were examined macroscopically and histopathologically at different time points (7th‑14th‑21st days PO). The safflower oil did not give successful results in preventing PIA when used alone. The AG macerated oils, especially AG20, caused negative effects on the injured tissue/organ surfaces due to their high ratio of 2,4‑decadienal content. The macerated oils prepared with fresh Taşköprü Garlic in safflower oil (FG15 and FG20) at the rate of 0.1 mL were found successful agents to prevent PIA by intra-abdominal route without any irritant effect in rats. These oils are considered as low cost clinical/laboratory preparations and can be used in laparotomy/laparoscopy to prevent PIA
Keywords: 3. Good health